2013
DOI: 10.1039/c3mb70172g
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic regulatory networks mediated by oncogene-driven microRNAs and transcription factors in serous ovarian cancer

Abstract: Although high-grade serous ovarian cancer (OVC) is the most lethal gynecologic malignancy in women, little is known about the regulatory mechanisms in the cellular processes that lead to this cancer. Recently, accumulated lines of evidence have shown that the interplay between transcription factors (TFs) and microRNAs (miRNAs) is critical in cellular regulation during tumorigenesis. A comprehensive investigation of TFs and miRNAs, and their target genes, may provide a deeper understanding of the regulatory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…TF–miRNA FFLs influence many biological processes mainly as noise buffering [13]. Over the past decade, TF–miRNA FFLs have been widely used to identify the cancer-associated genes or miRNAs in many tumor types, such as NSCLC [16], glioblastoma [14], ovarian cancer [15] and T-cell acute lymphoblastic leukemia [17]. However, such studies have focused on the individual tumor type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TF–miRNA FFLs influence many biological processes mainly as noise buffering [13]. Over the past decade, TF–miRNA FFLs have been widely used to identify the cancer-associated genes or miRNAs in many tumor types, such as NSCLC [16], glioblastoma [14], ovarian cancer [15] and T-cell acute lymphoblastic leukemia [17]. However, such studies have focused on the individual tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…The TF–miRNA FFL has been reported as motif that is overrepresented in regulatory network, and can minimize expression fluctuation against signaling noise [11]. During the past decade, network approach based on TF–miRNA FFLs has been demonstrated as a promising tool to dissect the etiology of many tumors [13], such as glioblastoma [14], ovarian cancer [15], non-small-cell lung cancer (NSCLC) [16] and T-cell acute lymphoblastic leukemia [17]. For example, Mitra et al identified the disrupted FFLs in NSCLC from a predicted, but reproducible, TF and miRNA regulatory network, and found that miR-9-5p and miR-130b-3p could inhibit the tumor-suppressive activity of TGF-β pathway by targeting a core regulatory molecule TGFBR2 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, miRNA(s) and TF(s) may regulate each other reciprocally and form a feed-back loop (FBL), or both can jointly regulate the expression of target genes and form a feed-forward loop (FFL) (Guo et al 2010). FFL-based combinatorial regulatory network approaches recently emerged as promising tools to elucidate complex diseases such as schizophrenia (Guo et al 2010), glioblastoma multiforme (Setty et al 2012;Sun et al 2012), ovarian cancer (Zhao et al 2013), and osteosarcoma (Poos et al 2013). However, current FFL studies mostly rely on the predicted regulation information, leading to high false positive rates.…”
Section: Introductionmentioning
confidence: 99%
“…HSD11B2 is the enzyme that regulates the glucocorticoid metabolism. The interaction between glucocorticoid and insulin is a very important signal for regulating long-term energy metabolism [64]. In particular, NR3C1, the downstream gene of HSD11B2, has been reported to be associated with glucocorticoid resistance, eating disorder and obesity [58,66].…”
Section: Discussionmentioning
confidence: 99%